Cucurbitane-Type Triterpenoids from the African Plant Momordica balsamina - Ramalhete, Catia (2015)
Phytochemical investigation of the aerial parts of Momordica balsamina led to the isolation of five new cucurbitane-type triterpenoids (1-5) and two known analogues (6, 7). Their structures were elucidated on the basis of spectroscopic methods including 2D NMR experiments (COSY, HMQC, HMBC, and NOESY). The new compounds feature unusual oxidation patterns in the cucurbitane skeleton, such as at C-29 (1-3) and C-12 (4, 5). Compounds 1-4, 6, and 7 were evaluated for in vitro cytotoxicity against human breast cancer cells (MCF-7), using the MTT assay.